Development of Interactive Animated Multimedia-Based Learning Tools in Improving Student Learning Outcomes Healthy Food Materials - Tatik Sugiwati; Srihandono Budi Prastowo; Mohammad Imam Farisi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to produce interactive animated multimedia learning tools that are valid, practical, and effective in improving student learning outcomes of healthy food materials. This method used research and development with the ADDIE model and designed quasi-experiments. The population of this study was the teacher council along with grade V students of SDN Tamanbaru, SDN Kebalenan, SDN Sobo, SDN Kertosari 1, SDN Kertosari 2, and SDN Model. With samples of SDN Kebalenan (N = 28) as the experimental class and SDN Sobo (N = 28) as the control class. Assessment instruments were in the form of questionnaires, written tests, and observations. The data analysis techniques used were validity, reliability, normality, pair sample t-test, homogeneity, and independent t-test. The results showed: 1) Interactive animated multimedia devices, very feasible to use and valid with a value of 93.33%. The average reliability of 92.6 in the Excellent Reliability category; 2) Interactive animated multimedia devices, very practical with the ability to manage learning in experimental classes by 94.5% and student responses by 91.2%; 3) Interactive animated multimedia devices, very effective based on independent t-test data, with the significance value of Levene's test 0.189 > 0.05. The value of significance equality of means 0.002 < 0.05. While the statistically independent t-test group in the experimental class was 75.61 and the control class 64.86. Thus, interactive animated multimedia learning tools are valid, practical, and effective to be used in the learning process of healthy food materials.